Socio-eco-efficiency analysis of highways: a data envelopment analysis - Tatari, Omer; Egilmez, Gokhan; Kurmapu, Dhruva (Journal of Civil Engineering and Management, 2016)
To ensure the large network of highways is performing sustainably, there is a dire need to quantify sustainability for highways. In this paper, data envelopment analysis (DEA) based mathematical model is developed to evaluate sustainability in an attempt to aid these efforts. Sustainability goals pertaining to the three dimensions of sustainability, social, economic and environmental, were utilized. Utilizing the developed model, sustainability scores of thirty highway sections were calculated and ranked accordingly. Percent improvement analysis was carried out to gain more insight. In addition, sensitivity analysis was carried out to understand how different values of input parameters impacted the socio-eco-efficiency of each highway section. The aim of the study was to show that DEA based sustainability assessment model could be used to evaluate highways and assist in strategic planning goals of transportation agencies. Results indicated that 22% to 47% reductions are required to be achieved on negative social and environmental impacts for the inefficiency highway sections to be 100% efficient while keeping the economic indicators the same.